THE EFFECT OF ISLAMIC SERVICE QUALITY, PERCEIVED EASE AND RISK ON INTEREST IN USING BRI SYARIAH MOBILE BANKING WITH TRUST AS AN INTERVENING VARIABLE ΈCASE STUDY OF MAGELANG CITY COMMUNITYΉ - Muhammad Irfan Tolabi; Abdul Aziz; Oumar Tidiane Doumbouya (Imara: JURNAL RISET EKONOMI ISLAM, 2021)
The Effect of Islamic Service Quality, Perceived Ease and Risk on Interest in Using BRI Syariah Mobile Banking with Trust as an Intervening Variable (Case Study of Magelang City Community). The purpose of this study was to determine and analyze the effect of Islamic Service Quality (X1) Perceived Easiness (X2) Risk (X3) on Interest in Using Mobile Banking (Y) with Trust as an Intervening Variable (Case Study of Magelang City Community). The method used to collect data by distributing questionnaires to the people of Magelang City. The sample used in this study were 101 respondents with a purposive sampling technique. Then the data obtained were processed with SPSS Version 23. The analysis used in this study included instrument tests, statistical tests, classical assumption tests, and path analysis.Based on the results of the t test, it shows that Islamic service quality has a positive and significant effect on public interest, perceived convenience has a positive and insignificant effect on public interest, risk has a positive and insignificant effect on community interest, Islamic service quality has a positive and significant effect on public trust, perceived convenience has a positive and significant effect on public trust, risk has a positive and insignificant effect on public trust, trust has a positive and significant effect on public interest, trust is able to mediate Islamic service quality positively and significantly on public interest, trust is able to mediate perceived ease of interest community positively and significantly, trust is able to positively and significantly mediate the risk to public interest